Ireland and migration in the twenty-first century - Gilmartin, Mary, 1969- (Book collections on Project MUSE., 2015)
Migration is one of the key issues in Ireland today. This book provides a new and original approach to understanding contemporary Irish migration and immigration, showing that they are processes that need to be understood together rather than separately. It uses a wide range of data - from statistical reports to in-depth qualitative studies - to show these connections. The book focuses on four key themes - work, social connections, culture and belonging - that are common to the experiences of immigrants, emigrants and internal migrants. It includes a wide selection of case studies, such as the.